Transcriptional regulation of yeast phospholipid biosynthetic genes - Chen, Meng; Hancock, Leandria C.; Lopes, John M. (Biochimica et biophysica acta, 2007)
The last several years have been witness to significant developments in understanding transcriptional regulation of the yeast phospholipid structural genes. The response of most phospholipid structural genes to inositol is now understood on a mechanistic level. The roles of specific activators and repressors are also well established. The knowledge of specific regulatory factors that bind the promoters of phospholipid structural genes serves as a foundation for understanding the role of chromatin modification complexes. Collectively, these findings present a complex picture for transcriptional regulation of the phospholipid biosynthetic genes. The INO1 gene is an ideal example of the complexity of transcriptional control and continues to serve as a model for studying transcription in general. Furthermore, transcription of the regulatory genes is also subject to complex and essential regulation. In addition, databases resulting from a plethora of genome-wide studies have identified regulatory signals that control one of the essential phospholipid biosynthetic genes, PIS1. These databases also provide significant clues for other regulatory signals that may affect phospholipid biosynthesis. Here, we have tried to present a complete summary of the transcription factors and mechanisms that regulate the phospholipid biosynthetic genes.